Peculiarities of Lifestyle and Learning Motivation of 9th Grade Students in Cities and Rural Area Schools of Latvia - Porozovs, Juris; Miķelsone, Zane; Voita, Daina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Psychosocial problems of adolescents are related with their lifestyle but lifestyle and interests are affected by the area in which they live. The questionnaire of 9th grade students in 2 Latvia city schools and 2 Latvia rural area schools was carried out. The results of questionnaire showed that sport exercises in school attend majority of students in cities as well as in rural regions of Latvia but students from rural regions are more active. There are more students who spend less than 1 hour per day with their homework as well as watching TV in schools of Latvia cities in comparison with rural area schools. In Latvia cities as well as in rural regions students spend much time working with computer. The majority of students after 9th grade graduation intend to continue their studies in high school or vocational school.